066 Anti-thrombotic therapy and atrial fibrillation in Scotland: results of a national audit. (16th May 2012) - Simpson, J; Findlay, I N; Denvir, M; Murdoch, D L
Abstract : Introduction and Methods: GP practices across Scotland were invited to participate in an audit of the management of atrial fibrillation (AF) as part of a national audit of Clinical Standards in Heart Disease by Health Improvement Scotland. A primary care database interrogation tool was developed to identify patients with AF, extract relevant data and calculate a CHADS2 score for each patient. Results: 248 practices with a total practice population of 1 376 834 contributed data. 19 470 patients with AF were identified (prevalence 1.4%) including 18 165 patients with non-valvular AF. The majority of patients with non-valvular AF (56%) were in a high risk group for stroke (CHADS2 ≥2) and the most prevalent risk factors overall were age ≥75 (55%) and hypertension (56%). Formal stroke risk assessment was rarely recorded in primary care (<1%). 79% of patients with AF were prescribed some form of anti-thrombotic therapy, either anti-platelet or warfarin (Abstract 066 table 1 ). In the high risk group (CHADS2 ≥2) not on warfarin, a minority of patients had recorded exclusion criteria for warfarin (10%). In patients with non-valvular AF who had a prior history of ischaemic stroke or TIA, less than half (44%) were on warfarin. Conclusion: In Scotland, patients with AF are not receiving anti-thrombotic therapy according to guidelines. Patients at high risk of stroke are undertreated with warfarin and those at low risk of stroke are over prescribed warfarin. Strategies to improve appropriate anti-coagulant use in this group include routine use of simple stroke risk stratification.